A punição no sistema moral kantiano - Scariot, Juliane (My University, 2014)
This work constitutes an investigation about the purpose that Kant assigns to punishment in doctrine of duties and, therefore, analyzes the punitive questions related with doctrine of the Law, with doctrine of the Virtue (Ethic) and with doctrine of the Morals (Moral), well as their relations, at last the Moral, understood like a system composed of principles purely a priori, divides in Ethics and Law. The mentioned investigation begins with presentation of basic notions about the treatment spent for Kant to penalty, so that to explain what the philosopher understands by punitive justice, wrongdoing and punishment, well as present some polemic cases analyzed by him. In sequence, exposes and analyzes, critically, some possible interpretations to the Kantian writers about the punishment. Thereby, talks (i)about pure retributivism in your traditional version e in two sophisticated version, one with application of the notion of real negation and other defending the punishment like a kind of law defined by the criminal’s maxim; (ii)about partial retributivism stems from the perception of two punishment’s faces or of the social moral disapprobation that follows the penalty; (iii)about moral retribution and juridical utilitarism, that separates the punishments moral and juridical; (iv)about special prevention, understood like neutralization and resocialization. As from the verification of problems existents in interpretative possibilities established, proposes a construction of one new interpretation, based on a differentiation of Law, Ethic and Moral and in implications of this last (Moral) in the doctrine of the Law and of the Virtue. A new interpretation, in contrast to the traditional observation purely retributive, defends the existence of a preventive ambit of punishment, whose may be verified even in the book The Metaphysics of Morals, one of the latest works of Kant that would constitute the mature vision of this philosopher. That way, (a)the moral punishment have a merely retributive purpose, (b)there isn’t an ethical punishment, despite the existence of internal self-evaluation process, and (c)the juridical punishment have preventive and retributive finality. The dual purpose of juridical penalty stems from moral justification and its hypothetical necessity, as means to prevent the criminal occurrences. The mentioned purposes of juridical punishment are reached in three moments: (i)when considering the juridical sanction in the abstract that, contained in the criminal law itself intimidates the collectivity; (ii)in the determination, from the judge, of the penalty applicable to that particular case, because the magistrate must sets a retributive sanction, but, within the limits of retribution, must choose a penalty that prevents new crimes; (iii)in the execution of the penalty, since this phase allows that the condemned reeducate themselves and/or serve as an example to others. Finally, presents a subchapter with general clarifications that support the thesis of coherence in Kant writings about punishment.
Este trabalho constitui uma investigação sobre a finalidade que Kant atribui à punição na doutrina dos deveres e, portanto, analisa as questões punitivas relacionadas à doutrina do Direito, à doutrina da Virtude (Ética) e à doutrina dos costumes (Moral), bem como suas relações, afinal a Moral, entendida como um sistema composto por princípios puramente a priori, divide-se em Ética e Direito. A mencionada investigação inicia com a apresentação de noções básicas acerca do tratamento dispensado por Kant à pena, de forma a explicitar o que o filósofo entende por justiça punitiva, infração e punição, bem como apresentar alguns casos polêmicos analisados por ele. Na sequência, expõe-se e analisa-se criticamente algumas possíveis interpretações para os escritos kantianos sobre a punição. Assim, fala-se (i)do retribucionismo puro em sua versão tradicional e em duas versões sofisticadas, uma com a aplicação da noção de negação real e outra defendendo a punição como uma espécie de lei definida pela máxima do criminoso; (ii)do retribucionismo parcial decorrente da percepção de duas faces da punição ou da desaprovação moral social que acompanha a pena; (iii)da retribuição moral e do utilitarismo jurídico, que separa as punições moral e jurídica; (iv)da prevenção especial, entendida como neutralização e ressocialização. A partir da constatação dos problemas existentes nas possibilidades interpretativas postas, propõe-se a construção de uma nova interpretação, calcada na diferenciação de Direito, Ética e Moral e nas implicações da última nas doutrinas do Direito e da Virtude. A nova interpretação, ao contrário da tradicional visão puramente retributiva, defende a existência de um âmbito preventivo da punição, o qual pode ser verificado inclusive na obra A Metafísica dos Costumes, obra tardia de Kant que constituiria a visão madura do filósofo. Dessa forma, (a)a punição moral possui uma finalidade meramente retributiva, (b)não há uma punição ética, apesar da existência de um processo interno de autoavaliação, e (c)a punição jurídica possui finalidade preventiva e retributiva. A dupla finalidade da pena jurídica decorre de sua justificação moral e de sua necessidade hipotética, como meio para prevenir a ocorrência de crimes. As mencionadas finalidades da punição jurídica são alcançadas em três momentos: (i)quando se considera a sanção jurídica em abstrato que, contida na própria lei penal, intimida a coletividade; (ii)na determinação, pelo juiz, da pena aplicável àquele caso concreto, pois o magistrado deve fixar uma sanção retributiva, mas, nos limites da retribuição, deve escolher uma pena que previna novos crimes; (iii)na execução da pena, visto que essa fase possibilita que o condenado reeduque-se e/ou sirva de exemplo aos demais. Por fim, apresenta-se um subcapítulo com esclarecimentos gerais que corroboram a tese de coerência nos escritos de Kant sobre a punição.
Keywords: Kant, Immanuel; Direito e ética; Juízo (Ética); Ética